2004
DOI: 10.1023/b:bile.0000021955.27361.4b
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive responses to static conditions in nutrient-rich cultures of luminous Ralstonia eutropha

Abstract: The lux-gene fused Ralstonia eutropha, when adapting to static conditions, causes stratification of air-exposed and nutrient-rich cultures at above 0.15 mg biomass ml(-1). The O2 respiring biofilm (luminous neuston) phase, along with the dark sub-neustonic suspension phase, develops within 5-60 min. The instability of the biphasic static culture was identified as a reason for occasionally observable oscillatory bioluminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In related studies it was shown that bioluminescence from the millilitre-scale air-exposed samples of lux gene fused bacteria (known as whole-cell biosensors (12,13)) becomes unstable when the population density is sufficiently high (~0.10 mg biomass/mL) (14)(15)(16)(17). This phenomenon was called oscillatory bioluminescence.…”
Section: Introductionmentioning
confidence: 99%
“…In related studies it was shown that bioluminescence from the millilitre-scale air-exposed samples of lux gene fused bacteria (known as whole-cell biosensors (12,13)) becomes unstable when the population density is sufficiently high (~0.10 mg biomass/mL) (14)(15)(16)(17). This phenomenon was called oscillatory bioluminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Alcaligenes eutrophus AE1308, a transconjugant of A. eutrophus CH34 and A. eutrophus JMP134 (former name of C. necator JMP134) have been successfully used to form active biofilm into membrane reactor for wastewater treatment (Diels et al, 1995). Other studies carried out in different environments showed that strains similar to C. necator JMP134 were able to form biofilms: Ralstonia eutropha (Steinle et al, 1998; Simkus et al, 2004), Ralstonia solanacaerum (Tans-Kersten et al, 2001; Kang et al, 2002), A. eutrophus (Mergeay et al, 1985; VanRoy et al, 1997), Alcaligenes denitrificans (Elvers et al, 1998), Alcaligenes xylosoxydans (Meade et al, 2001). We did not measure exactly the surface area and thickness of the biofilm.…”
Section: Discussionmentioning
confidence: 98%